Some Granular Computing Based Machine Learning Algorithms - Vijay R. Tiwari (Transactions on Fuzzy Sets and Systems)
Granular computing has emerged as a new computational method that is beneficial when dealing with large amounts of data. In recent years, several machine learning models based on the granular framework have been developed, outperforming traditional machine learning models. This article reviews some newly developed techniques in terms of granular framework settings.